Wüstungen und Sozialbrache - Born, Martin (ERDKUNDE, 1968)
In the train of changes in social structure, many areas of Germany are characterised by a less intensive use of arable land, widely known as social dereliction (Sozialbrache). This tendency resembles in certain respects the abandonment of cultivated land during the desertion period of late medieval times. It should therefore be asked whether the contemporary contraction of agriculturally used land is not better described as field desertion. The term desertion (Wüstung) as used in late medieval and early modern sources refers to dwellings and larger complexes of arable land whose attribution for legal purposes of residence and taxation are unclear. Decisive for the designation as deserted was not the amount of used or unused arable land, but the falling away of former legal ties. In this connection the contemporary term field desertion is used for former arable now under woodland, whose former ownership parcelling is unknown. Because of this, fields affected by social dereliction, but whose ownership and economic-organisational details are still known, cannot be termed desertions. Only when the former field divisions of the abandoned land are masked by woodland, grass or shrub growth, is the use of the word desertion justified.